Federalism Concepts and Issues in Managing the Malaysian Water Sector - Md Khalid, Rasyikah; ., . (International Journal of Engineering and Technology, 2018)
Federalism refers to an agreement between several states which agree to be united as a nation state but with shared administrative responsibility. Under the dual federalism theory, the federal and the state governments are co-equals with specific powers granted by the constitution. In contrast, cooperative federalism denotes that although the federal government is supreme over the states, both acts cooperatively to solve common problem. Malaysia practices dual federalism as legislative powers of the federal and state governments are separated in the Federal Constitution. Rather than fostering cooperation, dual federalism in Malaysia has created tension between different levels of governments in the water sector as highlighted in the Selangor water woes. This paper evaluates issues arising in the Malaysian water sector from the federalism perspectives. Towards this end, doctrinal analysis on relevant laws and commentaries are made to appreciate the meaning of federalism and different approaches towards federalism. The paper concludes that different approaches towards federal-state relation can assist in improving the water sector and solve water conflict between different levels of governments in Malaysia.Â Â Â